Practical tips to nullify the pleasure of literature (Journal of Parents and Teachers, 2014)
This article presents a set of tips that can be very useful for our children or students to end up hating the literature. If we want young and young to read and become fond of reading and writing, here we have a perfect guide to what we do not have to do.
Keywords: literature; advice; nullify the pleasure of reading.